AKOMODASI DELIK LOKIKA SANGGRAHA DALAM PEMBARUAN HUKUM PIDANA - Dewa Ayu Widyani (to-ra, 2016)
In Balinese criminal customary law, there is there is an offense called lokika Sanggraha offense. Lokika Sanggraha is an offense committed by a man, where a man does not want to marry a woman who was pregnant with his child. This act is not a crime under the Criminal Code, however, a crime under the customary law. In this research, there are two problems, namely the punishment for the perpetrator of the lokika sanggraha offense and the prospects to accommodate lokika sanggraha offense in criminal law reform. The punishment for the perpetrators of the lokika Sanggraha conducted through the judge’s decision based on Article 359 Adhigama Scripture. In addition, the offender can be punished with custom obligations which aim to restore the balance. Prospects to accomadate lokika sanggraha offense in criminal law reform is very large considering criminal law reform must be done by exploring the values that live and thrive in the community. Sanggraha lokika offense can be used as one of the crimes in the offense of decency. Keywords: offense, criminal custom, lokika sanggraha.